Foreign exchange news announcements and the volatility of stock returns in Nigeria - Joshua Odutola Omokehinde; Matthew Adeolu Abata; Stephen Oseko Migiro (SPOUDAI - Journal of Economics and Business, 2017)
This paper examines the effect of foreign exchange news announcements on the volatility of stock returns in Nigeria, using the daily closing All-Share Index from The Nigerian Stock Exchange from 2000 to 2015. We extended existing literature by augmenting the EGARCH econometric model with exchange news announcements to specify both the conditional mean and volatility equations. The empirical results revealed a positive and significant effect of exchange news announcements on stock market volatility in Nigeria under symmetric conditional variance. However, there was strong evidence of asymmetric effect with negative exchange news which caused volatility to rise more following a large price rise than following a price fall of the same magnitude. The total impact of bad news had more distabilising effect on volatility than good news. The sum of ARCH and GARCH coefficients (» + Ø = 0.9) is approximately close to unity - indicating strong evidence of volatility persistence in the Nigerian stock market.
Keywords: C22; C58; G12; 330; volatility; stock returns; exchange news; asymmetric; volatility persistence